2003
DOI: 10.1103/physreva.68.042714
|View full text |Cite
|
Sign up to set email alerts
|

Electron-impact dissociation ofCH+ions: Measurement ofC+fragmen

Abstract: Absolute cross sections for electron-impact dissociation of CH ϩ producing C ϩ fragment ions were measured in the 3-100 eV range using a crossed electron-ion beams technique with total uncertainties of about 10% near the cross-section peak. Although the measured energy dependence agrees well with two sets of storage ring measurements, the magnitude of the present results lies about 15-25 % below the other results at the crosssection peak near 40 eV. Below 10 eV, the present data tend to exceed the storage ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
3
12
1
Order By: Relevance
“…The contribution of cross sections corresponding to 'pure' electronic excitation were estimated using Franck-Condon factors and these were then subtracted out to get the dissociation cross sections. Our results agree reasonably well with the measurements of Bannister et al (2003) from the threshold (10 eV) to about 18 eV and are within 20% of the measured values. Above this we would expect our results underestimate the cross section due to neglect of higher lying states which were not included in our calculations.…”
Section: Electron Impact Dissociationsupporting
confidence: 91%
See 3 more Smart Citations
“…The contribution of cross sections corresponding to 'pure' electronic excitation were estimated using Franck-Condon factors and these were then subtracted out to get the dissociation cross sections. Our results agree reasonably well with the measurements of Bannister et al (2003) from the threshold (10 eV) to about 18 eV and are within 20% of the measured values. Above this we would expect our results underestimate the cross section due to neglect of higher lying states which were not included in our calculations.…”
Section: Electron Impact Dissociationsupporting
confidence: 91%
“…A Multi Channel Quantum Defect Theory (MQDT) study of dissociative recombination of CH + and its isotopologue CD + was reported by Carata et al (2000) which were not in very good quantitative agreement with an earlier experimental study reported by Amitay et al (1996). Bannister et al (2003) reported an experimental study of the electron impact dissociation of CH + to the asymptotic states C + ( 2 P ) + H( 2 S). They measured absolute cross sections for electron impact dissociation of CH + ions producing C + ions.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Energy-resolved studies in this field were performed using crossed electron and molecular-ion beams, ranging from the earliest works in the late 1970s 1,2 and up to very recent studies. [3][4][5] However, internal excitation of the molecular ions introduces substantial ambiguities in the interpretation of these experiments, especially at collision energies of the order of 10 eV or below. During the last decade, studies of electron impact processes on internally cold molecular ions could be realized by using magnetic heavy-ion storage rings.…”
Section: Introductionmentioning
confidence: 99%